2016
DOI: 10.4236/jbnb.2016.71003
|View full text |Cite
|
Sign up to set email alerts
|

Mechanosynthesis as a Simple Method to Obtain a Magnetic Composite (Activated Carbon/Fe<sub>3</sub>O<sub>4</sub>) for Hyperthermia Treatment

Abstract: Mechanosynthesis as a Simple Method to Obtain a Magnetic Composite (Activated Carbon/Fe 3 O 4) for Hyperthermia Treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 34 publications
0
6
0
2
Order By: Relevance
“…The EDS images confirm that there is a peak of iron in MAC, which shows the presence of 25.67 wt % iron on the surface of MAC. Furthermore, a decrease in weight % of carbon is also observed in MAC compared to that of AC …”
Section: Resultsmentioning
confidence: 85%
“…The EDS images confirm that there is a peak of iron in MAC, which shows the presence of 25.67 wt % iron on the surface of MAC. Furthermore, a decrease in weight % of carbon is also observed in MAC compared to that of AC …”
Section: Resultsmentioning
confidence: 85%
“…The broad band between 3000-3700 cm -1 region is attributed to the hydroxyl groups. The peaks at 1094-1571 cm -1 are ascribed to the presence of active carbon [12,14]. Therefore, it can be concluded that Fe 3 O 4 nanoparticles were supported successfully on the palladium-carbon.…”
Section: Resultsmentioning
confidence: 78%
“…Nanokomposit magnetit karbon ini dapat meningkatkan kinerja adsorbsi sehingga sangat berpotensi menjadi adsorben magnetik untuk pengolahan air limbah [15], adsorben pewarna organik [20], adsorben pewarna tekstil serta memperbaiki sifat stabilitas kimia sehingga tidak mudah teroksidasi [19,24]. Nanopartikel magnetit yang dimodifikasi dengan karbon juga diketahui memiliki sifat adsorbsidesorpsi yang baik sehingga bisa diaplikasikan sebagai drug delivery [18,25].…”
Section: Latar Belakangunclassified
“…Kurva histeresis keduanya membentuk urut balik yang simetris ketika dikenai medan serta untuk magnetisasi memerlukan energi yang sangat kecil dengan nilai medan koersivitas Hc yang diperoleh sebesar 59, 37 [1]. Hal ini disebabkan karena karbon yang tidak memiliki sifat magnet atau bersifat diamagnet [41] maka, apabila dikompositkan karbon akan menurunkan sifat kemagnetan nanopartikel Fe3O4 [25,42].…”
Section: A Karakterisasi Vibrating Sample Magnetometer (Vsm)unclassified